Experimental research of the operation efficiency of the vortex diode for protection against water Hammer - Overko, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2016)
If the main cause of water hammer in a long discharge line is the sudden shutdown of the pump, it is enough to increase the reverse resistance of the discharge line for the protection against high pressure using large-size inkjet diodes, which have no moving parts and therefore are reliable, which is important for safety valves. Vortex diodes, the most important parameter of which is diodicity - the ratio of the reverse hydraulic resistance to forward best meet the requirements for reducing the water hammer magnitude. The description of the design of a new vortex diode with a conical inlet, the bench, the methodology of the experiments and the results obtained is given. A characteristic feature of the proposed design of the vortex diode is a conical inlet to the vortex chamber and the end arrangement of the offset on the outer surface. The flow characteristics of the diode in the reverse and forward fluid flow are built. The dependence of the diodicity on the flow rate is determined. It is shown, in particular, that this dependence is a third-order algebraic equation. The maximum diodicity is 12 at a water velocity of 3.8 m/s. The vortex diode time constant, which amounts to 1.35 s at the fluid velocity of 3.54 m/s, which confirms the adequacy of the numerical method for calculating the dynamic characteristics of vortex diodes is determined. The data are obtained in the simulation of the vortex diode operation by the numerical method.